MSG456 - Mathematical Programming February 2021 - PPSM, Pusat Pengajian Sains Matematik (Universiti Sains Malaysia, 2021)
Please check that this examination paper consists of THREE (3) pages of printed material before you begin the examination. Instructions : Answer FIVE (5) questions.